Evaluating reflective writing to guide curricular improvements in health informatics education. Issue 1 (2nd January 2022) - Lokker, Cynthia; Jezrawi, Rita
ABSTRACT: The use of reflective essays to guide curricular improvements is explored in this qualitative study of two cohorts of students enrolled in a graduate health informatics course. The research questions, methods, and analysis were co-designed with the course instructor and a student who had completed the course and was a teaching assistant in the subsequent year. We thematically analyzed 95 anonymized student reflective essays with a taxonomy of learning and codes developed using the assignment rubric and similar themes derived from published literature. Major themes that emerged were (1) foundational knowledge acquisition and understanding, (2) integration and critical reflection, (3) self-discovery and imagining possibilities beyond the course, and (4) sharing and the human dimension. The results reinforce strengths of the course and informs areas for curricular improvement that incorporate reflection as part of a summative assessment. The discussion highlights challenges students had in writing reflective essays, which will be used to refine the activity and the instructions for the assignment. Our findings will assist students in developing their reflective practice to carry forward in their experiential internship in the program and their careers.